Development and evaluation of oil-based formulations of entomopathogenic fungi for control of Sahlbergella singularis (Hemiptera: Miridae), a pest of cocoa in Africa - Mahot, H.C.; Hanna, R.; Mohab, J.R.; Begoude, B.A.T.; Membang, G.; Fotso Kaute, A.; Fiaboe, K.; Bagny-Beilhe, L.; Bilong-Biliong, C.F. (Informa UK Limited, 2025)
Sahlbergella singularis is the primary insect pest of cocoa in Western Africa. The current study determined the level of horizontal transmission of the entomopathogenic fungi (EPF) Beauveria bassiana (BIITAC6.2.2, BIITAC10.3.3) and Metarhizium anisopliae s.l. (MIITAC11.3.4 and MIITAC6.2.2) from infected to healthy target insects, the effect of various formulations, storage temperature on their conservation, and their efficacy to control S. singularis. Three vector ratios were used for inoculated to noninoculated insects, 1:4, 1:1, and 4:1, in addition to a control (0.1% v/v of Tween 80) without the EPF. Horizontal transmission of EPF from inoculated to noninoculated mirids varied from 25 to 75%. The formulation showed that the viability of conidia was significantly preserved in the invert emulsion formulation (IEF). Refined palm and cottonseed oils significantly maintained fungal conidia more viable than soybean and crude palm oils, and, therefore, had the best shelf life, respectively, with viable B. bassiana conidia (37.6 ± 6.05 CFU/ml) and M. anisopliae conidia (46.9 ± 8.8 CFU/ml). Formulated conidia tolerated a wide range of temperatures, 4°C, 15°C, 22°C, 25°C, and 30°C for B. bassiana and 4°C, 15°C, and 22°C for M. anisopliae. Under laboratory treatment for formulation efficacy against mirid, mortality confirmed by fungal growth reached 97.1% for IEF. In the cocoa field, the EIF of B. bassiana-based RPO caused a 100% population reduction compared with untreated plots on the 36th day after application. BITTAC6.2.2 and MIITAC11.3.4 strains showed the greatest biological control potential and could be promoted as part of a control strategy against cocoa mirid.